Ecclesiastical nationalism and primacy in world Orthodoxy: the case of the Serbian Church at the pan-Orthodox Council in Crete - Hofmeisterová, Karin (Religion, state & society, 2019)
The Holy and Great Council of the Orthodox Church (2016) was supposed to be, above all, a demonstration of Orthodox unity. However, four autocephalous Orthodox churches were absent and others were split internally over their stances towards the Council. Ethnophyletism (ecclesiastical nationalism) and disagreements between the Orthodox churches over universal primacy have often been emphasised as the factors which eventually prevented the display of full pan-Orthodox conciliarity. By analysing official documents of the Serbian Orthodox Church (SOC) and the statements of Serbian hierarchs, I assess the role of ethnophyletism and primacy in the SOC's positioning regarding the Council. I conclude that ethnophyletism and a lack of consensus over primacy were overshadowed by the cleavage between progressive and conservative tendencies within the SOC as well as beyond autocephalous frontiers. The study may thus contribute to a better understanding of the current challenges to pan-Orthodox conciliarity in general.